MODEL KEPEMIMPINAN PENDIDIKAN MASA DEPAN TINJAUAN DIMENSI AGAMA, FILSAFAT, PSIKOLOGI DAN SOSIOLOGI (Studi di Sekolah Tinggi Agama Islam Pangeran Dharma Kusuma Segeran Indramayu) - Arwani Arwani (Khulasah : Islamic Studies Journal, 2021)
This study aims to examine the future educational leadership model with a review of the foundations of religion, philosophy, psychology and sociology. The locus of this research is the Prince Dharma Kusuma Segeran Indramayu Islamic High School. This study uses a qualitative approach with descriptive analysis method. Interviews were conducted directly with informants, consisting of the Dean, Deputy Dean, Heads of the Program Study and Educational Staff and Non-Educational Personnel involved in the educational institution. The results of observations and documentation were obtained from various studies of documents, manuscripts, and archives related to the implementation of educational leadership at the Prince Dharma Kusuma Segeran Indramayu Islamic High School. The results of the study indicate that the educational leadership model for the future in the Segeran Indramayu Islamic High School after direct interviews with all parties involved in educational institutions can be explained in the discussion of this study. Keywords: Leadership and Future Leadership Model